“Why villagers stay put – A structural equation model on staying intentions” - Thomas Dufhues; Judith Möllers; Diana Traikova; Gertrud Buchenrieder; David Runschke (Journal of Rural Studies, 2021)
While the rural exodus dominates public and scientific debates, considerably less attention has been given to studying why the overwhelming majority of people worldwide remain immobile. As a consequence of this, the reasons why people stay, especially in economically weaker rural areas, are still not fully understood. This paper aims to contribute to closing this gap by addressing the question of why rural people stay put despite inter-regional welfare. Based on the Theory of Planned Behaviour (TPB) we model staying intentions of villagers in rural Kazakhstan, where many people leave toward urban areas. Our model focuses on staying behaviour, but explicitly includes the leave option as the alternative to staying, as well as both staying and leaving barriers. We apply a cutting edge partial least square structural equation model. Our study reveals the existence of an interaction between staying and leaving barriers. Thus, any policies reducing rural-urban migration barriers have a multiplier effect as people view staying as comparatively more difficult when leaving becomes easier. We further show that existing positive narratives of urban life weaken staying intentions. However, the strongest factor slowing rural exodus is not related to the rural economy, but to the future prossspects of children, including access to high-quality educational institutions in close proximity.
Keywords: 330; Central Asia; Kazakhstan; Migration; Non-migration; Theory of Planned behaviour; Partial least square modelling